Apatite fission track and (U-Th)/He thermochronology of Rochovce granite (Slovakia) - implications for thermal evolution of the Western Carpathian-Pannonian region - Danišík, Martin; Kohut, M.; Dunkl, I.; Hrasko, L.; Frisch, W. (Birkhäuser Verlag, Basel, 2008)
The thermal evolution of the only known Alpine (Cretaceous) granite in the Western Carpathians (Rochovce granite) is studied by low-temperature thermochronological methods. Our apatite fission track and apatite (U-Th)/He ages range from 17.5 ± 1.1 to 12.9 ± 0.9 Ma, and 12.9 ± 1.8 to 11.3 ± 0.8 Ma, respectively. The data thus show that the Rochovce granite records a thermal event in the Middle to early Late Miocene, which was likely related to mantle upwelling, volcanic activity, and increased heat flow. During the thermal maximum between ~17 and 8 Ma, the granite was heated to temperatures ~>60 °C. Increase of cooling rates at ~12 Ma recorded by the apatic fission track and (U-Th)/He data is primarily related to the cessation of the heating event and relaxation of the isotherms associated with the termination of the Neogene volcanic activity. This contradicts the accepted concept, which stipulates that the internal parts of the Western Carpathians were not thermally affected during the Cenozoic period. The Miocene thermal event was not restricted to the investigated part of the Western Carpathians, but had regional character and affected several basement areas in the Western Carpathians, the Pannonian basin and the margin of the Eastern Alps.